EFEKTIVITAS METODE KIBAR BERBASIS PENDEKATAN TALAQQI TERHADAP KEMAMPUAN MEMBACA AL-QUR'AN SISWA SDPLUS AL GHIFARI - Amelia, Nina; Wahyuni, Sri; Nikmah, Fathiyah; Kariadinata, Rahayu; Wulan, Elis Ratna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to analyze the effectiveness of the KIBAR Method based on the talaqqi approach in improving students’ Qur’anic reading skills at SD Plus Al-Ghifari. The study employed a quantitative approach using a pre-experimental method with a One Group Pretest-Posttest Design. The sample consisted of 170 first- and second-grade students enrolled in KIBAR Group 1. Data were collected through Qur’anic reading tests administered before and after the treatment. Data analysis was conducted using normality testing, the Wilcoxon Signed Rank Test, and N-Gain analysis. The normality test results indicated that the pretest and posttest data were not normally distributed; therefore, hypothesis testing was performed using the Wilcoxon Signed Rank Test. The Wilcoxon test yielded a significance value of 0.000 (< 0.05), indicating a significant difference between students’ Qur’anic reading abilities before and after the implementation of the treatment. Furthermore, the N-Gain analysis produced an average score of 63.44%, which falls into the moderately effective category. These findings indicate that the KIBAR Method based on the talaqqi approach is effective in improving students’ Qur’anic reading skills. The systematic structure of the KIBAR Method, combined with the direct guidance and corrective feedback provided through the talaqqi approach, contributed to the improvement of students’ Qur’anic reading abilities.